2022
DOI: 10.1038/s41598-022-14468-4
|View full text |Cite
|
Sign up to set email alerts
|

The genetic consequences of captive breeding, environmental change and human exploitation in the endangered peninsular pronghorn

Abstract: Endangered species with small population sizes are susceptible to genetic erosion, which can be detrimental to long-term persistence. Consequently, monitoring and mitigating the loss of genetic diversity are essential for conservation. The Peninsular pronghorn (Antilocapra americana peninsularis) is an endangered pronghorn subspecies that is almost entirely held in captivity. Captive breeding has increased the number of pronghorns from 25 founders in 1997 to around 700 individuals today, but it is unclear how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Repeated analysis has supported the differentiation of Peninsular and Sonoran subspecies from the American (Klimova et al 2014, Hahn et al 2020, 2021). Unsurprisingly, populations that have undergone recent bottlenecks have lost genetic diversity and become more genetically distinct from nearby populations; this pattern has been documented in Sonoran (Stephen et al 2005 a , Klimova et al 2014, Hahn et al 2021) and Peninsular (Klimova et al 2014, 2022) semi‐captive populations, in populations on the National Bison Range in Montana (Dunn et al 2011), and in a re‐introduced population in Oregon (Stephen et al 2005 b ). Lee et al (1989) documented low genetic diversity in Trans‐Pecos populations of pronghorn, and they suggested that the genetic structure of the herds were confused by multiple, poorly documented translocation events from outside of the region.…”
Section: Resultsmentioning
confidence: 96%
“…Repeated analysis has supported the differentiation of Peninsular and Sonoran subspecies from the American (Klimova et al 2014, Hahn et al 2020, 2021). Unsurprisingly, populations that have undergone recent bottlenecks have lost genetic diversity and become more genetically distinct from nearby populations; this pattern has been documented in Sonoran (Stephen et al 2005 a , Klimova et al 2014, Hahn et al 2021) and Peninsular (Klimova et al 2014, 2022) semi‐captive populations, in populations on the National Bison Range in Montana (Dunn et al 2011), and in a re‐introduced population in Oregon (Stephen et al 2005 b ). Lee et al (1989) documented low genetic diversity in Trans‐Pecos populations of pronghorn, and they suggested that the genetic structure of the herds were confused by multiple, poorly documented translocation events from outside of the region.…”
Section: Resultsmentioning
confidence: 96%
“…For example, Yucca schidigera populations in the BCP ( F ST = 0.067), as well as the endemic Yucca capensis ( F ST = 0.02) (De la Rosa‐Conroy et al., 2019 ; Luna‐Ortiz et al., 2021 ). Moreover, two subspecies of Agave cerulata from the north of the BCP also showed low genetic differentiation ( F ST = 0.098; Navarro‐Quezada et al., 2003 ), as did populations of Agave palmeri in Arizona ( F ST = 0.04; Lindsay et al., 2018 ), Agave angustifolia , in the Sonora state of Mexico ( F ST = 0.076; Klimova, Gutiérrez‐Rivera, et al., 2022 ), and Agave potatorum in southern Mexico ( F ST = 0.08; Ruiz‐Mondragón et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA from 98 individuals of Agave aurea sensu Webb and Starr ( 2015 ) was extracted using a modified hexadecyltrimethylammonium bromide (CTAB) protocol from the frozen leaf tissue disrupted with liquid nitrogen (Doyle & Doyle, 1987 ; Klimova, Gutiérrez‐Rivera, et al., 2022 ; Klimova, Mondragón, et al., 2022 ). The DNA quality was checked on a 1% agarose gel.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Population management in zoos has included an explicit focus on genetic diversity for over twenty years, with methods based on pedigree data proving efficient in mitigating the diversity loss [23][24][25][26][27][28]. However, challenges often arise when pedigree records are incomplete or inaccurate [29,30].…”
Section: Introductionmentioning
confidence: 99%